HLA-B and cysteinylated ligands distinguish the antigen presentation landscape of extracellular vesicles - Julia Bauzá-Martinez (Nature Portfolio, 2021)
Bauzá-Martinez et al. analyzed the HLA-I peptide ligandome in extracellular vesicles (EVs) from an EBV-immortalized B cell line, JY, and compare HLA-I-binding peptides recovered from EVs to those recovered from whole-cells. The authors report an enrichment for HLA-B-binding peptides and for post-translationally modified cysteinylated peptides in EVs as compared to whole-cells.